2015
DOI: 10.5558/tfc2015-071
|View full text |Cite
|
Sign up to set email alerts
|

Applications of visual magnitude in forest planning: A case study

Abstract: Recent impacts from the Mountain Pine Beetle epidemic, the lack of available timber in areas of lower elevation, and the reduction in back-country timber has pushed forest operations into publicly significant and visible landscapes. When these become the stage for operations they can be a source of public backlash. These kinds of landscapes are carefully protected by governments, yet, this protection may reduce timber availability. We have developed a new GIS-based tool to aid planners in designing harvests in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The method presented here is not only applicable for understanding scenic areas from social media users' photographic locations. It can also be used to visualise the visual impact of proposed park management, such as forestry or road construction, and therefore help guide the mitigation of significant visual impacts (Chamberlain et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The method presented here is not only applicable for understanding scenic areas from social media users' photographic locations. It can also be used to visualise the visual impact of proposed park management, such as forestry or road construction, and therefore help guide the mitigation of significant visual impacts (Chamberlain et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, decision- makers may reject proposed landscape management when using the traditional viewshed for fears of it degrading the view, but in reality, the area of proposed management may only account for an infinitesimally small proportion of the viewer's field of view. This difference is likely to be introduced by pixels closer to the viewpoint often being assigned a greater visual magnitude weighting as land cover closer to the user will often take up a greater proportion of the field of view (Chamberlain and Meitner, 2013;Chamberlain et al, 2015).…”
Section: Objective 2: Effect Of Viewshed Methods Land Cover Visibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The imagery of flood impacts accompanying flood projections (Keller et al 2006) and hurricane storm surge forecasts (Rickard et al 2017;Wilhelmi et al 2023) have been shown to increase information comprehension and risk perception. Evaluation of three-dimensional (3D) visualizations, fourdimensional (4D) time-enabled animations, and immersive augmented and virtual reality (Chamberlain et al 2015(Chamberlain et al , 2016Unreal Engine 2018;Tomkins and Lange 2019;Stempel and Becker 2021;Bernhardt et al 2019) also showed improvement in information comprehension and risk perception and generated new knowledge on how people perceive space and place (Bruns and Chamberlain 2019). These examples illustrate the potential to improve risk communication through geovisualizations, especially when cartographic elements and visual representations of risk connect people to their environment or, broadly speaking, to a place.…”
Section: Introductionmentioning
confidence: 99%
“…Visibility (viewshed) analysis has been applied to a range of applications in forest ecosystems, from locating fire watchtowers (Bao et al, 2015;Göltaş et al, 2017), hiding scars from timber harvest (Chamberlain et al, 2015;Domingo-Santos et al, 2011), planning military operations (Caldwell et al, 2005;Drummond, 1956), to studying animal spatial behavior (Dupke et al, 2017;. However, despite the successful application of visibility analysis in natural resource management, previous studies indicate that measurement of fine-scale visibility in forest environments, particularly at the landscape level, is a challenge considering the architectural complexity of the plant (Murgoitio et al, 2014) which causes objects such as animals to be obscured (camouflaged) by vegetation.…”
Section: Introductionmentioning
confidence: 99%